2008
DOI: 10.2460/ajvr.69.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carprofen on the integrity and barrier function of canine colonic mucosa

Abstract: Carprofen increased in vitro conductance and permeability to mannitol in canine colonic mucosa. Carprofen resulted in sloughing of cells and erosion of the colonic mucosa. These findings suggested that carprofen can compromise the integrity and barrier function of the colonic mucosa of dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Recent incidental reports suggest that carprofen administration to dogs alters functions of platelets, which are relevant to the repair sequence [17]. Also, carprofen has been shown to compromise the integrity and barrier function of the gastrointestinal mucosa in dogs [18]. The present data, which expand on a previous short communication [5] unequivocally demonstrate that carprofen can interfere significantly with anastomotic integrity in the rat small bowel.…”
Section: Discussionsupporting
confidence: 71%
“…Recent incidental reports suggest that carprofen administration to dogs alters functions of platelets, which are relevant to the repair sequence [17]. Also, carprofen has been shown to compromise the integrity and barrier function of the gastrointestinal mucosa in dogs [18]. The present data, which expand on a previous short communication [5] unequivocally demonstrate that carprofen can interfere significantly with anastomotic integrity in the rat small bowel.…”
Section: Discussionsupporting
confidence: 71%
“…38 In that study, 38 mild epithelial sloughing was observed in 5 of 63 (7.9%) sections, moderate sloughing was observed in 17 of 63 (27.0%) sections, and severe sloughing was observed in 41 of 63 (65.0%) sections. 38 In that study, 38 mild epithelial sloughing was observed in 5 of 63 (7.9%) sections, moderate sloughing was observed in 17 of 63 (27.0%) sections, and severe sloughing was observed in 41 of 63 (65.0%) sections.…”
Section: Necrosis Of Cells Sloughing Of Epithelium Within Gastric Glamentioning
confidence: 70%
“…38 In that study, 38 mild epithelial sloughing was observed in 5 of 63 (7.9%) sections, moderate sloughing was observed in 17 of 63 (27.0%) sections, and severe sloughing was observed in 41 of 63 (65.0%) sections. 38 It was suggested that sloughing of cells and erosions likely contributed to an increase in electrical conductance and permeability recorded in carprofen-treated sections, compared with findings in untreated control samples. 38 Edema was not evident in 16 of 63 (25.4%) sections but was rated mild in 37 (58.7%) and moderate in 10 (15.9%) sections.…”
Section: Necrosis Of Cells Sloughing Of Epithelium Within Gastric Glamentioning
confidence: 70%
See 2 more Smart Citations